AVALIAÇÃO DO NÍVEL DE CONFORTO TÉRMICO DE ESCOLA INFANTIL COM PROJETO-PADRÃO - Ritter, Viviane; Modler, Nébora; Maciel, Thalita; Freitas, Franciele; Cunha, Eduardo; Rheingantz, Paulo Afonso (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper relates the results of a thermal comfort analysis of a School of Early-Childhood Education of the Proinfancia Program, with a standard and a modified design, located in a municipality in the Bioclimatic Zone 2, State of Rio Grande do Sul, Brazil. The method was structured in two parts: a walkthrough analysis was performed based on the Experiential Approach covering all parts of the built environment; and a three-stage computational simulation - modeling, simulation and analysis - of the thermal comfort level of the building considering the adaptative model from ASHRAE 55. The results emphasize: the difficult and the importance of approaching the occupancy profile of the environments in the simulations; the importance of the computer simulations for the arguments construction and procedures to modify habits, values, and practices of the designers and the occupants of the environments; and they also qualify our predictions and prescriptions for the real usage of the internal spaces, produced by the users, in order to the spaces can better meet their demands and wishes of well-being.